2007
DOI: 10.1002/qua.21314
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic potential–density relationships in molecules

Abstract: ABSTRACT:In this work, we present Hartree-Fock and density functional theory nuclear electrostatic potential-density relationships for several homonuclear diatomic molecules. The results of our calculations are encouraging with relatively low errors in the energies. Implications for the application of this work to novel molecular energy equations as well as the need for further improvement of these newly proposed relationships in molecules have been addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The systems proposed suggested that a cluster anion consisting of water and HF molecules could trap electrons in a cyclic Á Á Á FH Á e Á HF Á Á Á bridge. The electron was found to be relatively stable with a VDE of around of 5.41 eV for the (FH) 5 Á eÁ (HF) 5 system, which was found to be the most stable orientation towards electron detachment. In this molecule, extensive internal hydrogen bonding led to an increased stability of the system, which in turn resulted in more stable anions.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The systems proposed suggested that a cluster anion consisting of water and HF molecules could trap electrons in a cyclic Á Á Á FH Á e Á HF Á Á Á bridge. The electron was found to be relatively stable with a VDE of around of 5.41 eV for the (FH) 5 Á eÁ (HF) 5 system, which was found to be the most stable orientation towards electron detachment. In this molecule, extensive internal hydrogen bonding led to an increased stability of the system, which in turn resulted in more stable anions.…”
Section: Introductionmentioning
confidence: 94%
“…The progress of the study of molecular electron traps based on the works of our group and the works of others over the last few years was the focus of the recent review [5]. The issue of the intra-molecular versus the surface electron binding to water clusters of various sizes was the focus of a recent report by Jordan [6].…”
Section: Introductionmentioning
confidence: 98%